2020
DOI: 10.1186/s12874-020-00958-4
|View full text |Cite
|
Sign up to set email alerts
|

Telephone versus web panel National Survey for monitoring adoption of preventive behaviors to climate change in populations: a case study of Lyme disease in Québec, Canada

Abstract: Background: To monitor the adoption of climate change adaptive behaviors in the population, public health authorities have to conduct national surveys, which can help them target vulnerable subpopulations. To ensure reliable estimates of the adoption of these preventive behaviors, many data collection methods are offered by polling firms. The aim of this study was to compare a telephone survey with a web survey on Lyme disease with regard to their representativeness. Methods: The data comes from a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Diferentes áreas do conhecimento, incluindo as Ciências Sociais, Políticas, do Comportamento e da Comunicação, as têm utilizado e discutido desde então as possíveis limitações e necessidades de avanços metodológicos 3,4,5 . De modo geral, websurveys podem ser realizadas utilizando-se cadastros de endereços de e-mail (membros de uma categoria profissional ou estudantes de uma universidade, por exemplo 6,7 ), painéis de usuários da Internet 8,9 ou a divulgação do link da pesquisa em websites e redes sociais 10,11 . Considerando que cada uma dessas apresenta suas características, o foco será dado a websurveys que incluem voluntários recrutados em websites e redes sociais.…”
unclassified
“…Diferentes áreas do conhecimento, incluindo as Ciências Sociais, Políticas, do Comportamento e da Comunicação, as têm utilizado e discutido desde então as possíveis limitações e necessidades de avanços metodológicos 3,4,5 . De modo geral, websurveys podem ser realizadas utilizando-se cadastros de endereços de e-mail (membros de uma categoria profissional ou estudantes de uma universidade, por exemplo 6,7 ), painéis de usuários da Internet 8,9 ou a divulgação do link da pesquisa em websites e redes sociais 10,11 . Considerando que cada uma dessas apresenta suas características, o foco será dado a websurveys que incluem voluntários recrutados em websites e redes sociais.…”
unclassified
“…The respondents were generally more educated (large effect size) and had a higher household income (large effect size). The proportions of respondents aged between 65 to 74 and older than 75 years old are lower than the proportion in the target population (small effect size) [84,85].…”
Section: Main Studymentioning
confidence: 81%
“…Flu immunization rates are higher among adults aged 65 and over compared to younger age groups in Texas (Texas Health and Human Services 2021); therefore, these differences between BRFSS/CATI, which had a higher number of older adult respondents, and the other methods were unexpected. Other studies have reported variations in survey responses by protocol (Domche et al 2020;McMaster et al 2017).…”
Section: Discussionmentioning
confidence: 99%